2022
DOI: 10.1021/jacs.2c02676
|View full text |Cite
|
Sign up to set email alerts
|

Dioxane Bridge Formation during the Biosynthesis of Spectinomycin Involves a Twitch RadicalS-Adenosyl Methionine Dehydrogenase That May Have Evolved from an Epimerase

Abstract: Spectinomycin is a dioxane-bridged, tricyclic aminoglycoside produced by Streptomyces spectabilis ATCC 27741. While the spe biosynthetic gene cluster for spectinomycin has been reported, the chemistry underlying construction of the dioxane ring is unknown. The twitch radical SAM enzyme SpeY from the spe cluster is shown here to catalyze dehydrogenation of the C2′ alcohol of (2′R,3′S)-tetrahydrospectinomycin to yield (3′S)dihydrospectinomycin as a likely biosynthetic intermediate. This reaction is radical-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…It was hypothesized that the three observed products (i.e., 18-P , 10-P , and 11-P ) are produced sequentially beginning with C2′-methylation of 2′-dAMP ( 3 → 18-P , Figure A). OxsB then catalyzes dehydrogenation of the C2′-CH 3 methyl to yield the methylidene 10-P rather than a second round of methylation as observed in other radical-mediated methyltransferases. Although examples of radical SAM catalyzed dehydrogenation of alcohols, thiols, and amines are well-known, biological C-CH 3 dehydrogenase activity has not been previously reported for a radical SAM enzyme. Nevertheless, NosL from nosiheptide biosynthesis catalyzes C–C desaturation of a substrate structural analogue, and DarE from the darobactin maturation pathway has been identified to catalyze off-pathway dehydrogenation of the C α –C β bond of a tryptophan residue in its peptide substrate. , Once formed, 10-P could then serve as an acceptor for OxsB catalyzed addition of the 5′-deoxyadenosyl radical ( 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was hypothesized that the three observed products (i.e., 18-P , 10-P , and 11-P ) are produced sequentially beginning with C2′-methylation of 2′-dAMP ( 3 → 18-P , Figure A). OxsB then catalyzes dehydrogenation of the C2′-CH 3 methyl to yield the methylidene 10-P rather than a second round of methylation as observed in other radical-mediated methyltransferases. Although examples of radical SAM catalyzed dehydrogenation of alcohols, thiols, and amines are well-known, biological C-CH 3 dehydrogenase activity has not been previously reported for a radical SAM enzyme. Nevertheless, NosL from nosiheptide biosynthesis catalyzes C–C desaturation of a substrate structural analogue, and DarE from the darobactin maturation pathway has been identified to catalyze off-pathway dehydrogenation of the C α –C β bond of a tryptophan residue in its peptide substrate. , Once formed, 10-P could then serve as an acceptor for OxsB catalyzed addition of the 5′-deoxyadenosyl radical ( 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the B 12 -dependent radical SAM enzyme Her6 is proposed to catalyze the necessary epimerization of C3′–OH likely with 22 (with a 3′ S configuration) serving as the substrate. To date, no B 12 -dependent radical SAM enzyme has been reported to catalyze an epimerization reaction; however, radical SAM enzymes have been reported that do not depend on B 12 and are known to function as epimerases. Subsequent cyclization to form ring B of herbicidin after C3′ epimerization need not be enzyme-catalyzed. The final step in the biosynthesis of 2 is then proposed to be the reduction of 33 , which is hypothesized to be catalyzed by Her7.…”
Section: Resultsmentioning
confidence: 99%
“…Most aminoglycosides have a 2deoxystreptamine (2-DOS) moiety as an aglycone, with different amino-sugars attached to the carbons 4 and 5 or 4 and 6 such as in kanamycin, gentamicin, and neomycin [8]. In recent years, there were great advances in the understanding of biosyntheses and in the enzymology of several biosynthetic steps from aminoglycosides, particularly those 2-DOS-containing molecules [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%